Video confirmation of head impact sensor data from high school soccer players - Patton, D. A.; Huber, C. M.; McDonald, C. C.; Margulies, S. S.; Master, C. L.; Arbogast, K. B. (The American Journal of Sports Medicine, 2020)
Background: Recent advances in technology have enabled the development of head impact sensors, which provide a unique opportunity for sports medicine researchers to study head kinematics in contact sports. Studies have suggested that video or observer confirmation of head impact sensor data is required to remove false positives. In addition, manufacturer filtering algorithms may be ineffective in identifying true positives and removing true negatives.